2019
DOI: 10.12659/msm.914908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Submucosal Tunneling Endoscopic Resection (STER) and Other Resection Modules for Esophageal Muscularis Propria Tumors: A Retrospective Study

Abstract: Background Surgery has been considered to be the primary approach for resection of esophageal muscularis propria tumors. With the development of endoscopic technology, new techniques such as endoscopic submucosal dissection (ESD) and submucosal tunneling endoscopic resection (STER) have emerged for resecting these lesions. Previous studies have demonstrated that STER might be an intriguing alternative. This study aimed to evaluate the clinical value of STER by comparing it to other resecting modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…In this study, we found that the procedure duration of mark-guided STER was shorter compared with several previous studies, whereas the en bloc resection rate of mark-guided STER was prominently higher than that of these studies [ 15 , 16 , 21 ]. However, multivariate logistic regression demonstrated that procedure duration was an independent factor associated with en bloc resection.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In this study, we found that the procedure duration of mark-guided STER was shorter compared with several previous studies, whereas the en bloc resection rate of mark-guided STER was prominently higher than that of these studies [ 15 , 16 , 21 ]. However, multivariate logistic regression demonstrated that procedure duration was an independent factor associated with en bloc resection.…”
Section: Discussioncontrasting
confidence: 54%
“…Several techniques, including endoscopic submucosal dissection (ESD), endoscopic submucosal enucleation (ESE), endoscopic full-thickness resection (EFR), thoracoscopic enucleation, and submucosal tunneling endoscopic resection (STER), have been proved to be effective for esophageal SMTs [10][11][12][13]. However, STER is gradually recommended because it possesses more advantages than ESD, ESE, EFR, and thoracoscopic enucleation [14][15][16]. In 2012, inspired by peroral endoscopic myotomy (POEM), STER was firstly developed to remove esophageal SMTs originating from the MP layer [17].…”
Section: Introductionmentioning
confidence: 99%
“…In one patient with an early submucosal cancerous lesion at the thoracic esophagus in our study, the left gastric lymph nodes were fused into a big mass, which indicates the necessity of resecting the upper stomach together with its mesogastrium and left gastric artery lymph nodes besides radical resection of the cancer itself. This may suggest incomplete resection of esophageal submucosal cancer by EMR, ESD, and endoscopic full-thickness resection [ 13 19 , 39 42 ]. If the esophageal submucosal cancer was just resected locally without removing the upper stomach including the left gastric lymph nodes and mesogastrium, a high proportion of patients with esophageal submucosal carcinomas will have cancer metastasis to the left gastric lymph nodes, resulting in recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Common adverse events included capno-mediastinum and subcutaneous emphysema, which were managed non-operatively[ 26 ]. When compared to other resection procedures such as ESD, no difference was seen in the rates of complications between the two procedures[ 30 ]. A retrospective study evaluated 137 patients with esophageal SMTs originating from the MP layer.…”
Section: Submucosal Tunneling Endoscopic Resectionmentioning
confidence: 99%
“…However, when compared to ESD, STER had longer operation times and lower en bloc resection rates. All patients were found to be free from local recurrence and metastasis after a 22-mo follow up[ 30 ].…”
Section: Submucosal Tunneling Endoscopic Resectionmentioning
confidence: 99%